Synchronous spawning of nursery-raised elkhorn coral (Acropora palmata) outplanted to reefs in the Florida Keys (United States) - Williams, Dana E.; Bright, Allan J.; Williamson, Olivia M.; Moura, Amelia; Ladd, Mark C. (Frontiers in Marine Science, 2023)
Here, we provide the first reports of spawning activity by Acropora palmata colonies outplanted to reefs in Florida, USA. In 2020, we observed light spawning from A. palmata colonies five years after they had been outplanted on two Florida reefs. In 2021 and 2022, we observed outplanted A. palmata colonies spawning synchronously with other nearby (<3 m) outplants and wild colonies more than 100 m away. During the 2022 spawning event, some colonies spawned in as few as four years after they had been outplanted. Among all spawning seasons, gametes collected from the outplanted colonies yielded high fertilization rates and viable larvae. These observations are promising for A. palmata restoration as they indicate fragments of A. palmata can spawn four years after outplanting and that efforts to restore A. palmata may be close to achieving the first step towards self-sustaining populations that can produce viable larvae, resulting in an increase in the population’s genotypic diversity upon successful recruitment to the reef.